Further education in transition - Joyce Martin; John Brown; Jean MacDonald; Meg Gain (Association for Learning Technology, 2000)
In 1992 the Further and Higher Education Act created the English further education sector by taking colleges out of LEA control and bringing into existence the Further Education Funding Council (FEFC). As in higher education (HE), similar funding arrangements exist for further education in Scotland, Wales and Northern Ireland.